2009
DOI: 10.3168/jds.2008-1153
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weaning method on health status and rumen development in dairy calves

Abstract: In the artificial rearing of dairy calves, the same feeding plan is applied to all animals during the milk-feeding period, with individual differences attributable to development or health status rarely considered. The aim of this study was 1) to analyze whether the parameters of feeding behavior automatically recorded by a feeding computer and weight gain are suitable for predicting the health status and rumen development of male dairy calves, and 2) to compare a conventional weaning method (end of milk provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
89
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 24 publications
(27 reference statements)
18
89
1
7
Order By: Relevance
“…These data may be used to identify sick calves (Svensson and Jensen, 2007;Borderas et al, 2009;Roth et al, 2009). Decreases in concentrate consumption have been correlated with decreased health status (Roth et al, 2009). Indeed, we found a tendency (P = 0.09) for decreased concentrate consumption in calves with BRD compared with that in healthy matched controls on the day BRD was identified.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…These data may be used to identify sick calves (Svensson and Jensen, 2007;Borderas et al, 2009;Roth et al, 2009). Decreases in concentrate consumption have been correlated with decreased health status (Roth et al, 2009). Indeed, we found a tendency (P = 0.09) for decreased concentrate consumption in calves with BRD compared with that in healthy matched controls on the day BRD was identified.…”
Section: Discussionsupporting
confidence: 55%
“…Calves on the H and M planes of nutrition were allowed a It may be possible to identify sick calves using feed-related data generated by electronic calf milk replacer (MR) and concentrate feeding systems. It has previously been shown that decreases in concentrate consumption, recorded by an electronic calf concentrate feeding system, were correlated with decreased health status and increased veterinary treatments (Roth et al, 2009). Sick calves have been observed to decrease their unrewarded visits to the MR feeder (Svensson and Jensen, 2007).…”
Section: Feeding Behaviour Recorded By the Electronic Feedersmentioning
confidence: 97%
See 1 more Smart Citation
“…Considering the intake of 700 g day −1 concentrate (Quigley III, 1996;Campos and Lizieire, 2000) to carry out weaning, the calves that received concentrate with 240, 160, 80, and 0 g kg −1 crude glycerin included could have been weaned at 40, 42, 44, and 46 days of age, respectively (Figure 1). This difference is significant when expenses with feeding and labor, milk commercialization, and animal performance are considered (Roth et al, 2009;Hulbert et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Locomotor play is also reduced at weaning but the correlation between energy intake and locomotor play is variable (Krachun et al, 2010;Sweeney et al, 2010;Rushen and de Passillé, 2012) and the relationship with growth rate is unknown. Adjusting the weaning age of calves according to their individual intakes of solid feed can prevent the drop in energy intake and growth after weaning, but results in greater differences between calves in weight gains (WGs) during and immediately after weaning, and in the age and duration of weaning (Roth et al, 2009;de Passillé and Rushen, 2012). However, it is not known how this method of weaning affects locomotor play.…”
Section: Introductionmentioning
confidence: 99%